Colonial anthropology
1 online resource
Keywords: "This book examines the process of domination of a civilisation and the creation of a vast empire by the British in India in the late 19th and early 20th century. It explores how they extended and maintained their tenuous rule over India through coercion, violent oppression and exploration of knowledge of this vast region and its people. Excavating archival materials, this volume looks at extensive ethnographic surveys, the study of history, cartography, archaeology, native languages and literatures from colonial times. It takes a critical look at the attempts at unraveling the social structural principles such as caste and religious groups and also how power was used in multiple forms and contexts to establish dominance over the people of the subcontinent and its resources. The essays in this volume are from a period when the technologies of colonization were being experimented with and reflect a mixed bag of admiration, derogation and paternalism from those holding positions of power and responsibility, including some elite Indians. It further examines the emergence of a sense of nationalism, a critique of the Eurocentric views of the colonial masters, indicating the contribution of Western education to the formation of an Indian identity that finds resonance in modern times. This book will be useful to students and researchers of anthropology, sociology, public administration, modern history, colonial studies, and demography. It will also be of interest to civil servants, students of history, Indian culture and society, religions, colonial history, law, and South Asia studies"--